MBE grown preferentially oriented CdMgO alloy on m- and c-plane sapphire substrates. (15th June 2022) - Adhikari, A.; Lysak, A.; Wierzbicka, A.; Sybilski, P.; Reszka, A.; Witkowski, B.S.; Przezdziecka, E.
Abstract: Unlike other II-VI semiconductors, CdO-based transparent oxide has great potential application for the fabrication of many optoelectronic devices. In this work, we study the growth of Cdx Mg1-x O alloys on m- and on c- plane sapphire substrates in Cd-rich to Mg-rich conditions using the plasma-assisted molecular beam epitaxy method. A structural and morphological study of CdMgO random alloys was carried out using X-ray diffraction and Atomic Force Microscope (AFM) techniques whereas composition analysis was done by Energy-dispersive X-ray (EDX) spectroscopy method. The optical properties of thin films were investigated by UV–Vis spectroscopy at room temperature. X-ray analysis confirmed the presence of cubic rock salt structure with <111> CdMgO crystallographic orientation on c -plane sapphire and <110> CdMgO preferential orientation on m -plane sapphire. The surface roughness was measured by the AFM. From the absorption curve, the optical bandgaps were determined using Tauc relation and it was found that the bandgap of films is influenced by the incorporation of Mg 2+ ions into the CdO lattice. Bowing parameter was calculated for both samples on m - and c -sapphires. Highlights: Ternary CdMgO cubic alloy films are prepared by PA-MBE technique. Better crystallographic results are obtained for CdMgO on m-plane sapphire. Direct and indirect bandgap increases with an increase in Mg content in the alloys. Morphological property changes in Cd-rich to Mg-rich CdMgO alloys.